2015
DOI: 10.1590/abd1806-4841.20153311
|View full text |Cite
|
Sign up to set email alerts
|

T regulatory cells (TREG)(TCD4+CD25+FOXP3+) distribution in the different clinical forms of leprosy and reactional states

Abstract: BACKGROUNDLeprosy is characterized histologically by a spectrum of different granulomatous skin lesions, reflecting patients' immune responses to Mycobacterium leprae. Although CD4+CD25+ FoxP3+ T regulatory cells are pivotal in the immuneregulation, presence, frequency, and distribution of Tregs in leprosy, its reactional states have been investigated in few studies.OBJECTIVESThis study aimed to verify the frequency and distribution of regulatory T cells in different clinical forms and reactional states of lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
(51 reference statements)
2
13
0
5
Order By: Relevance
“…The co-evolution of Mycobacterium and humans has resulted in Mycobacterium-modulated host cell machinery, including de-novo host gene expression by demethylation of important immune response genes. [31][32][33][34] Chronic infections by Mycobacterium evade host recognition on a cellular level by measurable increases in Treg cell numbers and cellular functions. 35 Treg cells are believed deficient in numbers or function in diverse autoimmune diseases and induction through BCG therapy would be a first step in restoring the immune balance that has been quantified by only flow cytometric methods after BCG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-evolution of Mycobacterium and humans has resulted in Mycobacterium-modulated host cell machinery, including de-novo host gene expression by demethylation of important immune response genes. [31][32][33][34] Chronic infections by Mycobacterium evade host recognition on a cellular level by measurable increases in Treg cell numbers and cellular functions. 35 Treg cells are believed deficient in numbers or function in diverse autoimmune diseases and induction through BCG therapy would be a first step in restoring the immune balance that has been quantified by only flow cytometric methods after BCG.…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacterium especially in the form of tuberculosis and leprosy are known to create granulomas encircled with T-regulatory cells. 33 BCG induces a similar systemic induction of Treg cells 4 and supplements the decrease in systemic inflammation that also drives type 1 diabetes inflammation. 44 Epigenetic reprogramming of the host by diverse infections, including Mycobacterium tuberculosis, or beta-glycan, a component of Candida albicans occurs at the levels of key checkpoints, including methyltransferases and key steps in aerobic glycolysis such as HIF1α.…”
Section: Our 8-year Long Clinical Trial Of Monitoring Subjects Receivingmentioning
confidence: 99%
“…A higher IL‐10 production was also found in BALB/c mice at 8 months postinoculation compared to 5 months, suggesting an immunoregulatory role for IL‐10. The Treg cells were described as a population of CD4 + CD25 + FoxP3 + T cells that produce IL‐10 and TGF‐β characterized by innate and adaptive immune response regulation and in leprosy there are many studies showing the participation these cells . Thus, it is possible that the Treg cells are involved in the later phase of the infectious process (8 months postinoculation) in an attempt to limit the magnitude of the response to bacilly antigens and to prevent tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies showing the participation of regulatory T cells (Treg) in leprosy reported a higher expression of these cells in LL and BL patients, with increased production of IL‐10 and transforming growth factor‐β (TGF‐β), indicating the suppressor role of Treg cells in lepromatous leprosy . In addition to these cells, the participation of Th17 cells in TT/BT patients has been shown and reveals the predominance of cytokines related to the Th1/Th17 profile in the tuberculoid pole and Th2/Treg on the lepromatous pole …”
Section: Introductionmentioning
confidence: 99%
“…, poderia se postular que a HI representa uma forma onde não ocorra resposta imune reguladora expressiva. No entanto, Parente et al125 estudaram Foxp3 em 9 casos de HI e encontraram expressão da molécula em 100% deles. Encontraram aumento significativo na quantidade de Foxp3 na reação reversa comparando-se com a forma indeterminada, DT e VV.…”
unclassified